LARANGAN MEMINANG PASANGAN YANG MELAKUKAN TA’ARUF PERSPEKTIF MADZAHIBUL ARBA’AH - Nurmadani; Fauzan Syawal Akbar (SAMAWA, 2025)
This study attempts to examine the prohibition of proposing to a partner who is undergoing ta'aruf from the perspective of the four main schools of thought in Islam: Hanafi, Maliki, Syafi'i, and Hanbali. Ta'aruf is a process of introduction between two individuals that aims to get to know each other better before deciding to proceed to marriage. In this context, the legal issue of proposing to someone who is undergoing the ta'aruf process with another person has become a debate among scholars. Each school of thought has a unique view and different arguments in responding to this problem. This study uses a qualitative method with a descriptive analytical approach. Data were obtained through literature studies from various fiqh books and the views of contemporary scholars. The results of the study show that although there are differences in the details of the explanations and exceptions given by each school of thought, in general the four schools of thought agree that proposing to a partner who is undergoing ta'aruf with another person is a prohibited act. This prohibition is based on the principle of maintaining ethics, respecting the ongoing process, and avoiding conflict in society. Keywords: Prohibition, Ta'aruf, Couple, Madzahibul Arba'ah.